2020
DOI: 10.1021/acs.orglett.0c00549
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed α-Alkylation of Ketones with Secondary Alcohols: Access to β-Disubstituted Carbonyl Compounds

Abstract: An iron-catalyzed borrowing hydrogen strategy has been applied in the synthesis of β-branched carbonyl compounds. Various secondary benzylic and aliphatic alcohols have been used as alkylating reagents under mild reaction conditions. The ketones have been isolated in good to excellent yield. Deuterium labeling experiments provide evidence that the alcohol is the hydride source in this reaction and that no reversible step or hydrogen/deuterium scrambling takes place during the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…The deuterium experiments are consistent with a 1,4-addition of H 2 to chalcone and indicate the involvement of both the metal and the participating ligand in the transfer-hydrogenation pathways (Scheme 6). [107] The results obtained with 1 are similar to those reported using Mn [137] and Fe [110] bifunctional catalysts. In contrast, a Co-catalyzed alkylation of acetophenone with secondary alcohol led to a comparable deuterium incorporation at both αand β-positions owing to either reversible steps or a deuterium/hydrogen scrambling on the Co complex.…”
Section: Deuterium-labeling Experimentssupporting
confidence: 85%
See 1 more Smart Citation
“…The deuterium experiments are consistent with a 1,4-addition of H 2 to chalcone and indicate the involvement of both the metal and the participating ligand in the transfer-hydrogenation pathways (Scheme 6). [107] The results obtained with 1 are similar to those reported using Mn [137] and Fe [110] bifunctional catalysts. In contrast, a Co-catalyzed alkylation of acetophenone with secondary alcohol led to a comparable deuterium incorporation at both αand β-positions owing to either reversible steps or a deuterium/hydrogen scrambling on the Co complex.…”
Section: Deuterium-labeling Experimentssupporting
confidence: 85%
“…A comparison of the performances of reported protonresponsive catalysts was made (see, Scheme S2). It is apparent that 1 exhibits better catalytic efficacy in terms of lower base loading and higher TON and TOF values for both α-alkylation of ketones [38,110,121,[135][136][137][138] and β-alkylation of secondary alcohols. [87,94,104,106,139]…”
Section: β-Alkylation Of Secondary Alcohols Using Primary Alcoholsmentioning
confidence: 99%
“…Subsequently, they developed a one‐pot synthesis of α ‐methyl ketones from the corresponding allylic alcohol applying an isomerization‐methylation strategy (Scheme 31A) [131] . Later, Renaud and co‐workers developed an α ‐alkylation to access β ‐disubstituted carbonyl compounds directly in presence of 11 a [132] . Exclusive alkylation of various hindered aromatic ketones were achieved using secondary benzylic and aliphatic alcohols in good yields (Scheme 31B).…”
Section: Alkylation Reactionsmentioning
confidence: 99%
“…[2] Exploiting this feature, we reported the iridium-catalyzed a-alkylation of ketones using primary and secondary alcohols to give a-and b-branched compounds, respectively (Scheme 1 top). [2,3] In addition our group, and others, have shown that this strategy can be used to build ring systems of different sizes (especially six membered) by sequential hydrogen borrowing alkylation with diols (Scheme 1 top). [4] It is important to note that after alkylation the Ph* group can be readily cleaved using a Br 2mediated retro Friedel-Crafts acylation, with the resulting acid bromide converted into a variety of different carboxylic acid derivatives, aldehydes or alcohols.…”
mentioning
confidence: 99%
“…[4] It is important to note that after alkylation the Ph* group can be readily cleaved using a Br 2mediated retro Friedel-Crafts acylation, with the resulting acid bromide converted into a variety of different carboxylic acid derivatives, aldehydes or alcohols. [2,3] Recently, we have considered the exciting possibility of promoting additional transformations of reactive intermediates generated during the hydrogen borrowing sequence (oxidation, condensation and reduction). [5] In this context we proposed that a key cyclopropyl-substituted enone intermediate, arising from a hydrogen borrowing process with a cyclopropyl alcohol, would undergo an in situ vinyl cyclopropane rearrangement to give 5-membered ring systems (Scheme 1, bottom).…”
mentioning
confidence: 99%